Neutronic Calculations for Certain Americium Mixed Fuels and Clads in a Boiling Water Reactor - Düz, Mehtap (Frontiers in Energy Research, 2021)
In this study, a Boiling Water Reactor (BWR) design was made using the Monte Carlo (MCNPX) method. The reactor core in the designed BWR system was divided into the square lattice 8x8 type with a constant pitch of 30.48 cm. In this study, americium (Am), which is found in the minor actinidine (MA) of spent nuclear fuel known as nuclear waste from existing reactors, was used as fuel with the addition of oxygen and fluorine. In this study, AmO2 and AmF3 fuels at the rate of 0.02%-0.1% were used as Americium Mixed Fuels, and Zircaloy-2 (Zr-2), SiC and VC were used as clad. Neutronic calculations for certain Americium Mixed Fuels and clads were compared in the designed BWR system. In the BWR system designed in the study; keff, neutron flux, fission energy, heating and depleted Am were calculated. The three-dimensional (3-D) modelling of the designed BWR system was performed by using MCNPX-2.7.0 Monte Carlo method and the ENDF/B-VII.0 nuclear data library.